Effects of URB597, an inhibitor of fatty acid amide hydrolase (FAAH), on analgesic activity of paracetamol - Soukupová, Marie; Palazzo, Enza; De Chiaro, Maria; Gatta, Luisa; Migliozzi, Anna Lucia; Guida, Francesca; Luongo, Livio; Giordano, Catia; Siniscalco, Dario; De Novellis, Vito; Marabese, Ida; Krsiak, Miloslav; et al. (Neuro-endocrinology letters, 2010)
OBJECTIVES: Paracetamol is converted to an active metabolite AM404 via fatty acid amide hydrolase (FAAH). The aim of the present study was to ascertain whether a FAAH inhibitor URB597 antagonizes paracetamol analgesic activity (and to asses by this way the role of FAAH in analgesic activity of paracetamol). METHODS: The interaction between a FAAH inhibitor URB597 and paracetamol was investigated in the writhing test in mice using an isobolographic analysis. RESULTS: URB597 or paracetamol alone and in combinations produced dose-dependent antinociceptive effects. ED50 values were estimated for the individual drugs and an isobologram was constructed. The observed ED50 value for the URB57-paracetamol combination was 0.097 (0.062-0.247) mg/kg. This value did not differ significantly from the theoretical additive ED50 value for the URB597-paracetamol combination which was 0.108 (0.059-0.198) mg/kg. Thus, inhibition of FAAH by URB597 was not followed by the lack of analgesic activity in paracetamol. CONCLUSION: The present results suggest that the analgesic activity of paracetamol is not dependent solely on FAAH metabolic conversion to AM404 and that paracetamol exerts analgesic activity also by additional mechanisms.
Keywords: Animals; karbamáty; vztah mezi dávkou a účinkem léčiva; Pain Measurement; neopioidní analgetika; lékové interakce; Analgesics, Non-Narcotic; Drug Interactions; Linear Models; Mice; lineární modely; měření bolesti; myši; Amidohydrolases; Benzamides; Dose-Response Relationship, Drug; paracetamol; Male; Carbamates; benzamidy; Acetaminophen; zvířata; mužské pohlaví; amidohydrolasy